An Investigation of Professional Networks and Scholarly Productivity of Early Career Physical Therapy Faculty. Issue 2 (June 2019) - Becker, Betsy J.; Sayles, Harlan; Woehler, Meredith; Rost, Tony; Willett, Gilbert M.
Abstract : Introduction and Review of the Literature: Physical therapy (PT) faculty must retain a scholarly agenda. Active engagement and dissemination are challenging, especially for new faculty. Evidence suggests that faculty professional networks can improve performance and innovation. The aim of this study was to determine an effective network structure and composition for scholarly activity of early career PT faculty. Subjects: Early career faculty (less than 5 years of experience) with primary teaching and service/administrative duties who worked in accredited entry-level PT programs from institutions of varying Carnegie Classification levels. Data from 50 faculty were analyzed. Methods: Subject questionnaires gathered data for social network analysis (visualization and calculation of network structure and composition). Participants' scholarly activity was determined by curriculum vitae analyses. Multivariable ordinary least squares regression models were developed to determine associations between networks and scholarly productivity. Results: The results show evidence that a more open, less interconnected (ie, low density) network is associated with higher scholarly activity when controlling for the duration as a faculty member and whether the individual has an academic doctoral degree. Discussion and Conclusion: Key implications from this study include 1) faculty can be productive in their first 5 years regardless of their institution's Carnegie Classification, days on the job, and achievement of an academic doctoral degree; 2) an effective network for scholarly productivity is one that is open and less densely interconnected; and 3) there are practical strategies faculty and their mentors can take to make networks more effective. Abstract : Supplemental Digital Content is Available in the Text.